GLOBAL (BEST) TOGETHER WITH (OR AGAINST) LOCAL NETWORKS AND PRACTICES? LIQUID ENGINEERING AND THE USES PROGRAMME. (13th January 2020) - Robbins, Peter; Wield, David; Wilson, Gordon; Watkins, Andrew; MacPhail, Peter
Abstract: There is potentially tension between world class research and global standards on the one hand and local contexts of engineering and development practice on the other. One aims at scientific status and entirely new knowledge, suggesting just one standard of quality. The other at building products and processes that might bring socio‐economic development, often prizing pragmatism and bricolage. The UK‐funded programme 'Understanding Sustainable Energy Solutions in Developing Countries' (USES) was set up on the understanding that such tensions, if they exist, can be transcended. It was funded by two organisations, the UK Engineering and Physical Sciences Research Council and the UK international development agency, Department for International Development. This paper analyses the USES research programme, looking at the processes of its establishment, partnership building, the research undertaken and its early impact. The paper shows that the USES programme goes beyond 'normal' pure versus applied, research versus policy and low‐tech versus high‐tech dualities. Instead, it throws up a complex series of issues that require attention if research is to lead to long standing and sustainable economic and social development. The paper suggests that the concept 'liquid engineering' might be a good way to conceptualise the ways in which the programme, without denying the tensions of dualistic realities, has moved towards a more fluid process to take account of its multiple and complex goals. The programme highlights that progress can be made towards engineering and development being accepted as a legitimate area of engineering theory and practice. © 2020 John Wiley & Sons, Ltd.